Plyometric basketball training - Ana Nikolic (Turkish Journal of Kinesiology, 2018)
Plyometric basketball training represents a widely used training method whose purpose is to resist the gravity force, meaning jump height improvement, better start acceleration, short section sprint, and direction change movement. The aim of this work was to analyze former plyometric basketball training researches, as well as to consolidate conclusions relevant to established work object analysis. This work covers 22 surveys published during a period from 2008 till 2018, which are shown in a chronological order and analyzed thoroughly. Obtained results suggest that fully planned and performed plyometric training within a defined time period has statistically significant positive effects on basketball explosive capacities development.